Mechanism of action of miR-15a-5p and miR-152-3p in paraquat-induced pulmonary fibrosis through Wnt/β-catenin signaling mediation - Dong Liu; Yan Guan (PeerJ, 2024)
Background miRNAs are small, conserved, single-stranded non-coding RNA that are typically transported by exosomes for their functional roles. The therapeutic potential of exosomal miRNAs has been explored in various diseases including breast cancer, pancreatic cancer, cholangiocarcinoma, skin diseases, Alzheimer’s disease, stroke, and glioma. Pathophysiological processes such as cellular inflammation, apoptosis, necrosis, immune dysfunction, and oxidative stress are closely associated with miRNAs. Internal and external factors such as tissue ischemia, hypoxia, pathogen infection, and endotoxin exposure can trigger these reactions and are linked to miRNAs. Paraquat-induced fibrosis is a protracted process that may not manifest immediately after injury but develops during bodily recovery, providing insights into potential miRNA intervention treatments. Rationale These findings could potentially be applied for further pharmaceutical research and clinical therapy of paraquat-induced pulmonary fibrosis, and are likely to be of great interest to clinicians involved in lung fibrosis research. Methodology Through a literature review, we identified an association between miR-15a-5p and miR-152-3p and their involvement in the Wnt signaling pathway. This allowed us to deduce the molecular mechanisms underlying regulatory interactions involved in paraquat-induced lung fibrosis. Results miR-15a-5p and miR-152-3p play roles in body repair processes, and pulmonary fibrosis can be considered a form of reparative response by the body. Although the initial purpose of fibrotic repair is to restore normal body function, excessive tissue fibrosis, unlike scar formation following external skin trauma, can significantly and adversely affect the body. Modulating the Wnt/β-catenin signaling pathway is beneficial in alleviating tissue fibrosis in various diseases. Conclusions In this study, we delineate the association between miR-15a-5p and miR-152-3p and the Wnt/β-catenin signaling pathway, presenting a novel concept for addressing paraquat-induced pulmonary fibrosis.